Performance of analogue, digital and hybrid finite impulse response filter banks affected by realisation errors and noise. Issue 8 (1st October 2018) - Pinheiro, Marcos A. A; Petraglia, Antonio; Petraglia, Mariane R.
Abstract : In this study, the performance of analogue, digital and hybrid finite impulse response filter banks affected by coefficient errors, mismatches among sub‐processors, and noise is investigated. A simple yet important class, the so‐called time‐interleaved filter bank, is also considered. Analytic models are derived to properly describe the impact of these imperfections on the filter bank performance. An estimator for the signal‐to‐noise ratio of these filter banks is advanced, from which comparisons are made among a large variety of structures. Computer simulations are carried out to verify the theory.